ADOPTION OF OPEN SOURCE SOFTWARE IN MALAYSIAN ORGANIZATIONS - Yajid, Mohd Shukri Ab; kKhatibi, Ali; Johar; MGM (International Journal of Psychosocial Rehabilitation, 2020)
Malaysian organizations are well acquainted with software applications in current global world. It is the necessity to adopt some software to engage to process of management positively and efficiently, while the main constraint is to enumerate whether the application is proprietary or an open source. This study examined the constraint and elements which affect the open source software adaptation in Malaysian organizations. For such purpose, different aspects of data have been gathered while focusing many sectors of Malaysia. After implication of different methodologies, it is asserted that plenty of factors prevail in the application while some significance has also been enumerated where the responses were also different from plenty of organizations in accordance to the surveys done.